Nutrition and Inflammatory Biomarkers in Chronic Pancreatitis Patients. (13th August 2018) - Greer, Julia B.; Greer, Phil; Sandhu, Bimaljit S.; Alkaade, Samer; Wilcox, C. Mel; Anderson, Michelle A.; Sherman, Stuart; Gardner, Timothy B.; Lewis, Michele D.; Guda, Nalini M.; Muniraj, Thiruvengadam; Conwell, Darwin; et al.
Abstract: Background: Chronic pancreatitis (CP) patients frequently experience malabsorption and maldigestion, leading to micronutrient and macronutrient deficiencies. Comorbid diabetes and lifestyle habits, such as alcohol consumption, may impact nutrition status. Methods: We compared micronutrient antioxidant, bone metabolism, serum protein, and inflammatory marker levels in 301 CP patients and 266 controls with no known pancreatic disease. We analyzed serum prealbumin and retinol binding protein; vitamins A, D, E, and B12; osteocalcin; tumor necrosis factor‐α; and C‐reactive protein (CRP). We also evaluated biomarkers among subsets of patients, examining factors including time since diagnosis, body mass index, alcohol as primary etiology, diabetes mellitus, vitamin supplementation, and pancreatic enzyme replacement. Results: After correcting for multiple comparisons, CP patients had significantly lower levels than controls of the following: vitamin A (40.9 vs 45.4 μg/dL) and vitamin E (α‐tocopherol [8.7 vs 10.3 mg/L] and γ‐tocopherol [1.8 vs 2.2 mg/L]), as well as osteocalcin (7.9 vs 10 ng/mL) and serum prealbumin (23 vs 27 mg/dL). Both patients and controls who took vitamin supplements had higher serum levels of vitamins than those not taking supplements. Compared with controls, in controlled analyses, CP patients had significantly lower levels of vitamins A, D, and E (both α‐tocopherol and γ‐tocopherol). CP patients also had significantly lower levels of osteocalcin, serum prealbumin, and retinol binding protein, and higher CRP. Conclusions: CP patients demonstrated lower levels of selected nutrition and bone metabolism biomarkers than controls. Diabetes and alcohol did not impact biomarkers. Vitamin supplements and pancreatic enzyme replacement therapy improved nutrition biomarkers in CP patients.